2012
DOI: 10.1152/ajpcell.00057.2012
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid, HAS1, and HAS2 are significantly upregulated during muscle hypertrophy

Abstract: Hyaluronic acid (HA) is a component of the extracellular matrix (ECM) in most vertebrate tissues and is thought to play a significant role during development, wound healing, and regeneration. In vitro studies have shown that HA enhances muscle progenitor cell recruitment and inhibits premature myotube fusion, implicating a role for this glycosaminoglycan in functional repair. However, the spatiotemporal distribution of HA during muscle growth and repair was unknown. We hypothesized that inducing hypertrophy vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 57 publications
5
55
0
Order By: Relevance
“…three HAS proteins are expressed by myoblasts in skeletal muscle (25), but the consistent relationship observed herein between increased Has2 transcript expression and myogenesis both in vivo and in vitro suggested that Has2 is intimately involved in the process by which myoblasts differentiate and fuse to form syncytial muscle cells. To test this hypothesis, we performed Has2 knockdown in C2C12 myoblasts that were induced to differentiate.…”
Section: Knockdown Of Has2 During In Vitro Myogenesis Reduces Hyalurosupporting
confidence: 66%
See 1 more Smart Citation
“…three HAS proteins are expressed by myoblasts in skeletal muscle (25), but the consistent relationship observed herein between increased Has2 transcript expression and myogenesis both in vivo and in vitro suggested that Has2 is intimately involved in the process by which myoblasts differentiate and fuse to form syncytial muscle cells. To test this hypothesis, we performed Has2 knockdown in C2C12 myoblasts that were induced to differentiate.…”
Section: Knockdown Of Has2 During In Vitro Myogenesis Reduces Hyalurosupporting
confidence: 66%
“…Has2 upregulation occurs neonatally, prior to detection of hypertrophy, suggesting that Has2 could be associated with the cause of hypertrophy in Callipyge muscles. Very recent studies have also reported increases in hyaluronan synthesis in a model of compensatory hypertrophy (25). Increased expression of Has1 and Has2 mRNAs was observed in this synergistic ablation model of hypertrophy, supporting the possibility of HAS2 mediating muscle growth and hypertrophy.…”
supporting
confidence: 63%
“…Real time PCR amplification reaction mixture (25 l) contained 12.5 l of 2ϫ SYBR Green PCR master mix following the Bio-Rad protocol, 5 l of diluted RT product (1:20), and 0.5 M sense and antisense primer sets. The primer sequences of Has1/2/3 (29), and GAPDH (30) are as follows: Col1␣1 (m), forward, 5Ј-gagccctcgcttccgtactc-3Ј, and reverse, 5Ј-tgttccctactcagccgtctgt-3Ј; Has1 (m), forward, 5Ј-gaggcctggtacaaccaaaag-3Ј, and reverse, 5Ј-ctcaaccaacgaaggaaggag-3Ј; Has2 (m), forward, 5Ј-gagcaccaaggttctgcttc-3Ј, and reverse, 5Ј-ctctccatacggcgagagtc-3Ј; Has3 (m) forward, 5Ј-tggacccagcctgcaccattg-3Ј, and reverse, 5Ј-cccgctccacgttgaaagccat-3Ј; GAPDH (m), forward, 5Ј-tgtcatcatacttggcaggtttct-3Ј, and reverse, 5Ј-catggccttccgtgttccta-3Ј.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have demonstrated that both the MMP-1 (Wang et al, 2009) and the MMP-2 (Zimowska et al, 2008) have important effects on the migration and differentiation of skeletal muscle satellite cells both in in vitro cultured muscle cells and in in vivo animal models, including mdx mice (an X-link dystrophic skeletal muscle mouse model). Deletion of the MMP-2 gene significantly decreased the extent of hypertrophy observed in MMP-2 knockout mice (Zhang et al, 2014) and an up-regulation of MMP-2 following a hypertrophic stimulus (Calve et al, 2012). This suggests that MMP-2 is a pertinent contributor to muscle hypertrophy.…”
Section: Discussionmentioning
confidence: 87%